South Africa's Federated Identity Management Initiative - Mammen, Siju A. (My University, 2013)
An overview of the concepts involved with identity federation, focusing specifically on it as a means to complement the existing digital identity management infrastructure for research and educational institutions in South Africa, is provided. The paper juxtaposes traditional identity management ideas to the federated model. A description of the South African initiative to establish a pilot Federation is described. The novelty of the South African initiative is the approach that was followed. Specifically it has been driven in a top down fashion. This is compared with other approaches in establishing Federated Identity Management within the NREN community. The ultimate goal of which is to show the reader that several methods exist to establish a federation.
Keywords: Identity Management; SAML; Federation; Single-sign on